Impact of Synbiotic and Antibiotic growth promoter (AGP) Supplementation on Duodenal Morphology in Broiler Chicken - Ankur Pandey; Abhinov Verma; Shriprakash Singh; MM Farooqui; Archana Pathak; Varsha Gupta; Rupam Sinha; Anand Singh (Indian Journal of Veterinary Anatomy, 2025)
Under present investigation, ninety (n=90) day-old broiler chicks were reared and assigned to 03 treatments groups consisting of three replicates of 10 birds in each pen. It was divided into three groups viz; Group-I (control/basal diet feed), Group-II (antibiotic growth promoter-AGP treatment) and Group-III (synbiotic treatment) comprised of 30 birds in each group. A ventro-abdominal incision was made, and dissection was performed and different biometrical measurements of the duodenum were taken on the empty duodenum. Duodenum was the first segment of the small intestine which originated from the right antero-dorsal surface of the gizzard. In all age groups and experimental treatments, two bile ducts and two pancreatic ducts opened close to each other in the ascending part of the duodenum near its termination. The supplementation with synbiotics significantly increases weight, length and width of duodenum in broiler chickens as compared to control and AGP group. This increment in morphometric parameters might be corelated with the composition of the diet and the supplements used.